New business dynamics and agressiveness between competitors - Ochoa, Sandra Ruiz (2015)
Recent work has focused on analysing whether competitive advantages can be sustainable in a hypercompetitive context. Extant literature, which analysed emerging economies, found that the development of the institutional context contributes to creating hypercompetitive conditions. In this study was recognized the importance of these researches to the strategic management field but instead of focusing the attention on emerging countries, was considered necessary to take a broader spectrum as an object of study with countries that differ in their characteristics. This research also used a different methodology from the studies taken as a reference as the one made by Hermelo e Vassolo (2010) that focus its attention in developing countries, analysing the effect of institutions and hypercompetitive environments in the sustainability of competitive advantages. This research complemented those previous researches including data from firms in both, developing and developed countries to determine the difference in persistent superior economic performance over time between them, with the idea of showing how the environment is not only a key factor but also a main component in the development of competitive advantages. Using the Kolmogorov Smirnov test and the Propensity score matching to reduce bias, issues of sustainable competitive advantage and the effects of the institutional context in developed and developing countries was addressed, being careful with the comparison since their given differences might bring erroneous results. The empirical results support the proposition that there is a significant difference in superior economic performance and persistent superior economic performance sustainability between firms in countries with economic differences. Considering that this study focus on institutions and recognizing the importance they have in society and economic growth, studying them can help to determine how superior economic performance and persistent superior economic performance could be achieved with institution stability and favorable macroeconomic factors. An important contribution of this work is that it uses other theories related to the competitive advantages and connects the macroeconomic and institutional environment, with the purpose of comparing countries with different realities by statistical tests, giving answer to the formulated hypothesis.